Optical investigations using ultra-soft pseudopotential calculations of Si0.5Ge0.5 alloy - Y., Al-Douri; Y. P., Feng; A. C. H., Huan (Elsevier Ltd, 2009)
Link to publisher's homepage at www.elsevier.com